2015
DOI: 10.1159/000370239
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar Ataxia Type 7: A Neurodegenerative Disorder with Peripheral Neuropathy

Abstract: Background: Autosomal dominant spinocerebellar ataxias (SCA) are a group of inherited neurodegenerative disorders that typically show peripheral neuropathy. SCA7 is one of the rarest forms of SCA (<1/100,000 individuals). However, the disease shows a prevalence of ∼800/100,000 inhabitants in certain regions of Mexico. This low global prevalence may explain, at least in part, the isolated anecdotal and limited clinical data regarding peripheral neuropathy in SCA7 patients. Aim: To assess sensory and motor perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
(34 reference statements)
3
9
0
Order By: Relevance
“…The sensory component might also be affected as non-myelinated bers also show alterations. SCA7 140Q/5Q mice ndings parallel recent studies of SCA7 patients, who showed abnormal motor and sensory nerve conductions (12), and complement previous neuropathological evidence of degenerating signs in the dorsal root and anterior horn of patients' spinal cord (5,7). Like SCA7, other polyQ SCA patients are affected by peripheral neuropathy symptoms and peripheral nerve pathology was reported in other polyQ SCA model (59,60).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The sensory component might also be affected as non-myelinated bers also show alterations. SCA7 140Q/5Q mice ndings parallel recent studies of SCA7 patients, who showed abnormal motor and sensory nerve conductions (12), and complement previous neuropathological evidence of degenerating signs in the dorsal root and anterior horn of patients' spinal cord (5,7). Like SCA7, other polyQ SCA patients are affected by peripheral neuropathy symptoms and peripheral nerve pathology was reported in other polyQ SCA model (59,60).…”
Section: Discussionsupporting
confidence: 86%
“…Brain imaging reveals the prominent atrophy of the cerebellum's grey and white matters and the pons, a correlation between cerebellar volume decrease and motor impairment, and more prominent degeneration in lobule IX and X of cerebellum compared to other structures (1,3,5,(7)(8)(9)(10)(11). Neurophysiological studies suggest the existence of a critical sensorimotor peripheral neuropathy (5,12,13). Visual impairment is mainly due to severe loss of cone and rod photoreceptors (5,14).…”
Section: Introductionmentioning
confidence: 99%
“…However, as for many neurodegenerative disorders, the accuracy of clinical assessment has limitation due to variation in the age of onset and disease progression. The recent study on a large cohort of 50 patients originating from a founder mutation in Mexico has allowed the specific clinical characterization of adult-onset patients (> 18 years) and early-onset patients (≤ 18 years) and the new observation of frontal-executive deficits and sensory-motor peripheral neuropathy in SCA7 [35,40]. It is noteworthy that infantile forms are much more severe and cause multisystem disorder including failure to thrive, hypotonia, myoclonic seizures, and non-central nervous systems dysfunctions like congestive heart failure, patent ductus arteriosus, atrial septum defect, renal failure, hepatomegaly, muscle atrophy, capillary leak syndrome, and hemangioma [30,33,[41][42][43][44][45][46].…”
Section: Clinical and Neuropathological Featuresmentioning
confidence: 99%
“…Particularly in Veracruz, where its prevalence is estimated to be as high as 1/125. High SCA7 prevalence has also been reported in several other parts of the world ( La Spada, 1993 ; Johansson et al, 1998 ; Jonasson et al, 2000 ; Zaheer and Fee, 2014 ; Faruq et al, 2015 ; Salas-Vargas et al, 2015 ).…”
Section: Introductionmentioning
confidence: 65%